2004
DOI: 10.1177/153303460400300512
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Risk Assessment in Molecular Epidemiology of Cancer

Abstract: One out of four deaths in the USA is due to cancer. Identification of populations at risk of developing cancer is important as it provides opportunities for prevention and treatment of cancer. Biomarkers are measurable indicators of exposure effects and susceptibility or disease state, and are used to understand the mechanisms of cancer progression. In recent molecular epidemiology studies genomic, proteomic, and epigenomic markers have been utilized which exhibit high sensitivity and specificity for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…For example, DNA adducts and some enzymes such as sulfotransferase A1 and epoxide hydroxylase have been validated and used as biomarkers for cancer detection [32]. The current advances in proteomics technology enable the identification of specific biomarkers from complex biological specimens [28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, DNA adducts and some enzymes such as sulfotransferase A1 and epoxide hydroxylase have been validated and used as biomarkers for cancer detection [32]. The current advances in proteomics technology enable the identification of specific biomarkers from complex biological specimens [28].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that many factors can contribute to carcinogenesis in humans. In molecular epidemiology studies, biological effects are more frequently measured by biomarkers, which are divided into three categories: measures of internal dose, early biological response, and host susceptibility (6,7). Many studies have found the associations between PAH environmental exposure, whose internal dose is usually quantified by 1-hydroxypyrene (1-OHP) in urine, and an increase in the levels of carcinogen-DNA adducts, sister chromatid exchange, and chromosomal aberrations (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to define and classify cancer biomarkers using different approaches, but general consensus has yet to be established. Broadly, any biologically derived entity or processes which lead to a cancer diagnosis (in prognosis, screening and risk assessment), at the stage of diagnosis or post diagnosis (in therapy and treatment module) are potential candidates as cancer biomarkers [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Due to the vast explosion of knowledge over the past several decades, collectively and in multiple spheres of the biomedical sciences and technology development, different methods have been suggested to classify cancer biomarkers.…”
Section: Classification Of Cancer Biomarkersmentioning
confidence: 99%